Analysis of MyPertamina Application Acceptance Using a Modified Technology Acceptance Model (TAM) - M. Ailza Sifaul Anam; Asif Faroqi; Tri Lathif Mardi Suryanto (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The rapid development of digital technology has driven PT Pertamina to launch the MyPertamina application as a solution to support the efficient and transparent distribution of subsidized fuel. However, the implementation of this application has encountered various technical complaints from users, including bugs, registration difficulties, and transaction issues, raising concerns about public acceptance of the technology. This study aims to analyze the factors influencing the acceptance of the MyPertamina application using the Technology Acceptance Model (TAM), which is modified by incorporating external variables such as perceived trust, perceived risk, perceived security, and service quality. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze data from 391 respondents. The findings indicate that service quality, perceived usefulness, and perceived trust significantly affect the attitude toward use, which subsequently influences the intention to use the application. In contrast, perceived ease of use, perceived risk, and perceived security were found to have no significant effect on the attitude toward use. These results provide strategic insights for the development and improvement of MyPertamina's digital services to enhance public acceptance.